PERNIKAHAN DINI DI INDONESIA: FAKTOR DAN PERAN PEMERINTAH (PERSPEKTIF PENEGAKAN DAN PERLINDUNGAN HUKUM BAGI ANAK) - Ana Latifatul Muntamah; Dian Latifiani; Ridwan Arifin (Widya Yuridika, 2019)
Children are the most valuable assets for the sustainability of a country. Quality should be preferred over quantity. Even though the quantity is very large, it must be balanced with good quality. This paper aims to explain early marriage in terms of legal perspective and its relation to the deprivation of children's rights. With a qualitative approach, there are five reasons that the community legalizes early marriage, namely: the age limit of marriage (Law No. 1 of 1974), akil baliqh, sustenance, in order to reduce the family's economic burden and who is ideal to marry first. Early marriage also results in social problems, namely: divorce, weak family stability, gender discrimination, and parenting for children becomes less good. Everyone is allowed to marry in the hope that marriage takes place between men and women who are mature in terms of their age, thoughts, and actions. However, the problem that is very crucial nowadays in Indonesia is justifying early marriage, arguing that it has met the requirements in Law No. 1 of 1974 concerning Marriage. However, this should not be a benchmark that age is allowed to marry, but there must be many considerations in terms of maturity, maturity in thinking and acting. In order to avoid divorce especially at a young age. In fact, what happens in Indonesia, if the child is less than 16 years old, the religious court gives a dispensation for marriage due to reasons of pregnancy, religious faktors, economic faktors, and educational faktors. Even worse, there is a village in Indonesia that responds positively to underage marriage. There is an assumption that early marriage is a tradition that must be guarded because it is a heritage. There are many reasons that at the age of 20 it has not been legalized for marriage, which is one of them from the aspect of reproductive health. Then, for women they are very difficult to continue their education to a higher level because they have the responsibility to take care of their husbands.Kata kunci: Pernikahan Dini, Aspek Sosial dan Hukum, Hak Asasi Manusia, Anak